2018
DOI: 10.1063/1.5037676
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory surface hopping study of propane photodissociation dynamics at 157 nm

Abstract: The photodissociation dynamics of propane molecules has been studied using the quasiclassical trajectory surface hopping (TSH) method in conjunction with Tully's fewest switches algorithm. The trajectories are propagated on potential energy surfaces computed on-the-fly using the multiconfiguration and multireference ab initio method starting in the lowest excited singlet state (HOMO → 3s Rydberg state) of propane at 157 nm with the emphasis on the site specificity of atomic hydrogen elimination, molecular hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Many of the present interpretations align with the results of recent quasi-classical trajectory surface hopping calculations for the next larger alkane, propane (C 3 H 8 ), following excitation at l ¼ 157 nm, wherein it was concluded that most dissociations occur aer internal conversion to the S 0 PES, that the energy disposal in the resulting fragments is governed by dynamical rather than statistical factors, and that the three-body fragmentation processes occur sequentially. 46 (e) Implications for modelling the atmospheres of the gas giants This work provides detailed new insights into the VUV photochemistry of ethane. The results discussed in detail in the above subsections are summarised below in terms of their implications for modelling the atmospheres of the gas giants.…”
Section: C-h Bond Ssionmentioning
confidence: 99%
“…Many of the present interpretations align with the results of recent quasi-classical trajectory surface hopping calculations for the next larger alkane, propane (C 3 H 8 ), following excitation at l ¼ 157 nm, wherein it was concluded that most dissociations occur aer internal conversion to the S 0 PES, that the energy disposal in the resulting fragments is governed by dynamical rather than statistical factors, and that the three-body fragmentation processes occur sequentially. 46 (e) Implications for modelling the atmospheres of the gas giants This work provides detailed new insights into the VUV photochemistry of ethane. The results discussed in detail in the above subsections are summarised below in terms of their implications for modelling the atmospheres of the gas giants.…”
Section: C-h Bond Ssionmentioning
confidence: 99%
“…In this study, we have used trajectory surface-hopping (TSH) methodology as implemented in the NEWTON-X package . This methodology is similar to one used previously by our group to study the photodissociation of propyne and propane. , In brief, the potential energies, energy gradients, and nonadiabatic couplings are calculated using the COLUMBUS electronic structure program interfaced with NEWTON-X for integrating trajectories. Initially, the molecule is excited to the first singlet (S 1 ) state.…”
Section: Electronic Structure and Computational Detailsmentioning
confidence: 99%